CALCIUM CARBONATE ISOLATION FROM EGGSHELL TO MEET PHARMACOPOEIAL STANDARDS AND ITS EFFECTIVENESS AS AN ANTACIDS - SUPRIADI, DADIH; MILANDA, TIANA; C., ANIS YOHANA; MUCTARIDI; ABDASSAH, MARLINE (International Journal of Applied Pharmaceutics, 2023)
Objective: Calcium carbonate is widely used in the pharmaceutical field as excipients and therapeutic agents. Calcium carbonate can be obtained from limestone, chalk, marble and dolomite. Other alternative is from eggshell. Calcium carbonate source from eggshell has several advantages including higher calcium carbonate content, fewer contaminants metal limit, and more brittle. Therefore, in this study, calcium carbonate had been isolated from eggshells which was expected to meet the requirements of Indonesian Pharmacopoeia (sixth edition) and having activity as antacid. Methods: Calcium carbonate were isolated from eggshells by mechanically and physically organic separation. The quality of calcium carbonate was examined according to the Indonesian Pharmacopoeia parameters including loss on drying; acid-insoluble substance, magnesium and alkali salt; limit of arsenic, lead, iron, mercury, heavy metal, and barium. Additional physicochemical characterization of calcium carbonate including particle size analyzer, FTIR and XRD were compared with those of commercial calcium carbonate. Results: The results showed that the isolation produced 98.5±0.5 % of calcium carbonate. The calcium carbonate powder had an average size of 21±1.0 µm, while that of commercial was 8±1.3 µm. The resulted calcium carbonate revealed similar XRD patterns compared with that from commercial Calcium carbonate from the market. Based on database from FTIR instrument, the calcium carbonate sample had 99% similarity level compared with that from the reference. The sample of Calcium carbonate isolated from the eggshell (>mesh 100) had lower antacid activity (23.83 mEq) than that of commercial (24.56 mEq). Conclusion: Calcium carbonate from eggshell fulfilled the requirements of Indonesian Pharmacopoeia.